Effect of isometric exercises on rectifying upper body muscle imbalance among young elite badminton players - Mohamed Gasibat, Qais Mustafa (2024)
This study examined the effect of isometric exercise on muscle imbalance in young elite badminton players. The experimental research design was performed using pre-test-post-test methodologies. Approximately 80 participants in this study were Malaysian male (N = 42) and female (N = 38) elite badminton players. These participants demonstrated an average age and maturity level of 14.74 years and 2.05 Peak Height Velocity, respectively. Initially, the participants were assigned using random sampling into two groups. These groups then proceeded with their respective physical training routines. The experimental group followed a 12-week internal and external rotation isometric exercise regimen. Each exercise consisted of 5 repetitions, 5 s of hold, and 5 s of relaxation. This exercise was repeated for three sets (with a 1 min rest between sets) and was performed 3 times per week. Meanwhile, the physical training routines from the intervention conducted by the experimental group were ensured to be distinct in this study. The researcher then closely monitored and regulated both groups during the experimental duration. The non-dominant shoulder's internal and external rotation isometric exercises were only demonstrated for the experimental group. This study encompassed three key measurements: pre-test data collected before any intervention, post-test1 data after 4 weeks of isometric exercises (12 sessions), and post-test2 data after 12 weeks of isometric exercises (36 sessions). A MicroFET®2 digital handheld dynamometer was then employed to conduct the muscle imbalance assessment concerning the internal and external rotations of the dominant and non-dominant shoulders. The data were collected at a specialised facility in the Kuala Lumpur Badminton Association, Bukit Kiara, Kuala Lumpur, Malaysia, which was tailored explicitly for elite badminton players.